Headache Care in China. Issue 4 (25th March 2014) - Yu, Shengyuan; Zhang, Mingjie; Zhou, Jiying; Liu, Ruozhuo; Wan, Qi; Li, Yansheng
<x xml:space="preserve">Abstract</x> Headache disorders are problematic worldwide. China is no different. A population‐based door‐to‐door survey revealed that the 1‐year prevalence of primary headache disorders in China was 23.8%, constituting a major societal burden. Many headache centers and clinics have been established in China, and headache disorders (and associated stress) are receiving an increased level of expert attention. This review summarizes the outcomes of the epidemiological survey and the progress of clinical and basic research in China, describes the present situation in terms of headache diagnosis and treatment, and discusses the future of headache care in China.